CIPK23 regulates blue light‐dependent stomatal opening in Arabidopsis thaliana. (1st September 2020) - Inoue, Shin‐Ichiro; Kaiserli, Eirini; Zhao, Xiang; Waksman, Thomas; Takemiya, Atsushi; Okumura, Masaki; Takahashi, Hirotaka; Seki, Motoaki; Shinozaki, Kazuo; Endo, Yaeta; Sawasaki, Tatsuya; Kinoshita, Toshinori; et al.
SUMMARY: Phototropins (phot1 and phot2) are plant blue light receptor kinases that function to mediate phototropism, chloroplast movement, leaf flattening, and stomatal opening in Arabidopsis. Considerable progress has been made in understanding the mechanisms associated with phototropin receptor activation by light. However, the identities of phototropin signaling components are less well understood by comparison. In this study, we specifically searched for protein kinases that interact with phototropins by using an in vitro screening method (AlphaScreen) to profile interactions against an Arabidopsis protein kinase library. We found that CBL‐interacting protein kinase 23 (CIPK23) interacts with both phot1 and phot2. Although these interactions were verified by in vitro pull‐down and in vivo bimolecular fluorescence complementation assays, CIPK23 was not phosphorylated by phot1, as least in vitro . Mutants lacking CIPK23 were found to exhibit impaired stomatal opening in response to blue light but no deficits in other phototropin‐mediated responses. We further found that blue light activation of inward‐rectifying K + (K + in ) channels was impaired in the guard cells of cipk23 mutants, whereas activation of the plasma membrane H + ‐ATPase was not. The blue light activation of K + in channels was also impaired in the mutant of BLUS1, which is one of the phototropin substrates in guard cells. We therefore conclude that CIPK23 promotes stomatal opening through activation of K + in channels most likely in concert with BLUS1, but through a mechanism other than activation of the H + ‐ATPase. The role of CIPK23 as a newly identified component of phototropin signaling in stomatal guard cells is discussed. Significance Statement: This study indicates that CIPK23 is a phototropin‐interacting protein kinase that promotes blue light‐ and phototropin‐dependent stomatal opening in Arabidopsis thaliana . We propose that CIPK23 does not mediate plasma membrane H + ‐ATPase activation but mediates inward‐rectifying K + channel activation in stomatal opening.